Growth and Production Response of Mustard Plants (Brassica juncea L) Due to the Application of Chicken Manure Compost Enriched with Kirinyuh Plant Leaf Waste and Banana Stems - Maruapey, Ajang; Wati, Darma; Fajeriana, Nurul (Agrikan Jurnal Agribisnis Perikanan, 2023)
Organic materials of animal manure, green plant debris when composted into fertilizer are very useful as plant fertilizers, increase soil organic matter and improve the quality of soil health in a sustainable manner. The purpose of this study was to reveal the effect of chicken manure compost fertilizer on the growth and yield of mustard plants. The research was conducted in the farmer's garden of Matawolot Village, Salawati District, Sorong Regency, Southwest Papua Province. The experiment was conducted from May to July 2023 at an altitude of ± 15 m above sea level with flat topography. The experimental design used was a Randomized Group Design (RAK) with 4 treatments of chicken manure compost doses, namely; A0 = 0 kg plot-1, A1 = 2 kg plot-1, A2 = 4 kg plot-1, A3 = 6 kg plot-1. Each treatment was repeated 3 times so that 12 experimental plots were obtained. Each plot consisted of 16 plants, each plot was taken 5 plants as observation samples. The results of the study were analyzed using variance analysis. if the analyzed data showed significant differences among fertilizer treatments, then continued with the Least Significant Difference Test (BNT) at the 0.05% confidence level. The results proved that all variables measured due to compost fertilizer treatment gave optimal results. Thus the highest final yield obtained from this study reached 8.04-8.94 tons/ha.